BANKRUPTCY ANALYSIS OF STARTUP COMPANIES WITH USING THE Z-SCORE METHOD (ALTMAN) - Mukarram, Hadratul; Dipoatmodjo, Tenri S.P; Nurman; Anwar; Aslam, Annisa Paramaswary (Malaqbi Publisher, 2023)
This research aims to determine the potential bankruptcy of PT Bukalapak.com (BUKA) and PT Gojek Tokepedia Tbk (GOTO) using the Z-Score (Altman) method. The population in this study is the financial reports of PT Bukalapak.com (BUKA) and PT Gojek Tokepedia Tbk (GOTO), with a sample of the financial reports of PT Bukalapak.com (BUKA) from 2020 to 2022 and PT Gojek Tokepedia Tbk (GOTO) from 2020 to 2022. Data collection This research was carried out using the documentation method. The data analysis technique uses the Z-Score (Altman) model with the variables Working Capital to Total Assets, Retained Earnings to Total Assets, EBIT to Total Assets, and Book Value of Equity to Book Value of Debt. The results of this research show that in 2020 PT Bukalapak.com (BUKA) and PT Gojek Tokepedia Tbk (GOTO) were in bankruptcy because the Z-Score was below 1,10. In 2021-2022 PT Bukalapak.com (BUKA) and PT Gojek Tokepedia Tbk (GOTO) are in a healthy condition because the Z-Score is above 2,60.